2018
DOI: 10.5505/.2018.07269
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and Clinical Features of Young Adult Males Using Synthetic Cannabinoid (English)

Abstract: Object: Synthetic Cannabinoid (SC) use is becoming more widespread throughout the world. Studies that revealed user profiles indicate that the drug is especially popular among young men. Knowledge on sociodemographic, clinical characteristics and motivation for SC users in our country is limited. On the other hand, in spite of the increase of information known about symptoms of acute intoxication of SC use, physical and psychiatric consequences and loss of function due to longterm use of SC is limited. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
2
4
2
Order By: Relevance
“…Statistical analysis revealed no significant differences between survivors and nonsurvivors as regard age, sex, manner of poisoning and route of poisoning. Similar results obtained by Oznur et al (2018) in their study of 166 patients with SCs use where the age onset for SCs use was 17.25 ± 2.30 years, all the patients were males, and consumption of SCs was through inhalation (76.5%) or through oral route (22.9 %). Moreover, a Turkish research on 158 SCs users by Bozkurt et al (2014) revealed that 94.9% of SCs users were men, with mean age of 26.1±7 year.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Statistical analysis revealed no significant differences between survivors and nonsurvivors as regard age, sex, manner of poisoning and route of poisoning. Similar results obtained by Oznur et al (2018) in their study of 166 patients with SCs use where the age onset for SCs use was 17.25 ± 2.30 years, all the patients were males, and consumption of SCs was through inhalation (76.5%) or through oral route (22.9 %). Moreover, a Turkish research on 158 SCs users by Bozkurt et al (2014) revealed that 94.9% of SCs users were men, with mean age of 26.1±7 year.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, vomiting was noted in 33 % of the patients and 32% had respiratory distress and most of them (22%) were mechanically ventilated. Similarly Oznur et al (2018) in their study found that 62% of the SCs users had respiratory distress and 53% had vomiting.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, in another study by Öznur et al, 12 the mean age of patients was found to be 21.04 ± 1.04, which was younger than what was found in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…[14][15][16] In our study, 67.5% of cases were using synthetic cannabinoids daily, 10% were using 5 to 6 times, 17% used 3 to 4 times, and 5% once to twice per week. Öznur et al 13 found that 55% of cases use synthetic cannabinoids every day, 76.5% > 2 in a week. The most common accompanying agents to synthetic cannabinoid use in our study were in the form of tobacco and THC.…”
Section: Discussionmentioning
confidence: 99%